DISCRIMINANT MODELS SUSCEPTIBILITY TO LEVEL OF CARIES TEETH IN SOMATIC HEALTHY MEN FROM DIFFERENT REGIONS OF UKRAINE DEPENDING ON PECULIARITIES OF DERMATOGLYPHIC INDICATORS - Шінкарук-Диковицька, М.М. (World of Medicine and Biology, 2014)
The results of simulation using discriminant analysis, susceptibility to various intensity levels of tooth decay in somatically healthy men from different ethno-territorial regions of Ukraine (north, south, central, western and eastern), depending on the characteristics parameters of palmar and fingers dermatoglyphics. In men of southern and eastern regions of Ukraine developed quite correct discriminant model (as in the southern region Wilks lambda statistic = 0.078, and in the east - 0.219, p
Keywords: discriminant model; dermatoglyphics; somatically healthy men; the regions of Ukraine